Trauma: code red : companion to the RCSEng definitive surgical trauma skills course - Khan, Mansoor, 1977-; McMonagle, Morgan (Boca Raton, FL : CRC Press/Taylor & Francis Group, 2019)
The Royal College of Surgeons' of England two-day "definitive surgical trauma skills course "is run by the authors. The course began in 1997 but a new syllabus has recently been put in place.The focus is on thoracic,abdominal and vascular injuries, caused by both penetrating trauma, such as a knife, and ballistic trauma caused by guns.This Manual accompanies the course and it's aim is to "demystify the body "and show how to control massive blood loss. Interventions, whether they be military or civilian, are descrbed in full, and techniques derived from the battlefield and world-wide hotspots in trauma --are exemplified within this book.
Damage control -- Ballistics -- Airway -- Thoracic -- Vascular -- Fasciotomy -- Pelvis -- Trauma laparotomy -- Abdominal -- Future haemorrhage control.
OCLC-licensed vendor bibliographic record.
Keywords: Wounds and injuries -- Treatment; Traumatology; Emergency medicine; MEDICAL / Surgery / General; MEDICAL / Orthopedics; MEDICAL / Surgery / Vascular